Prolonged ketosis and glycosuria secondary to SGLT2 inhibitor therapy. Issue 11 (9th November 2021) - Bobrowski, David; Kumar, Reha; Wu, Peter E.; Lapointe‐Shaw, Lauren
Abstract: Clinicians should be aware of the potential for the pharmacologic activity of SGLT2 inhibitors to persist long after the standard drug clearance period of five half‐lives, the typical duration used to guide pre‐operative medication recommendations. Abstract : Clinicians should be aware of the potential for the pharmacologic activity of SGLT2 inhibitors to persist long after the standard drug clearance period of five half‐lives, the typical duration used to guide pre‐operative medication recommendations.